2018
DOI: 10.1002/jcla.22633
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐C3 ratio and neutrophil‐to‐lymphocyte ratio were associated with disease activity in patients with systemic lupus erythematosus

Abstract: NC R and NLR are two useful inflammatory markers for evaluating disease activity in patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…26 The observations were in line with that noted by . 27 Yu et al, based on a retrospective study involving 194 SLE patients and 71 healthy controls, have reported a significant positive correlation of SLEDAI with NLR, and a statistically significantly higher NLR in subjects with severe disease activity (>9 SLEDAI score) than mild disease activity (≤9 SLEDAI score). The current study has shown a significant correlation between SLEDAI and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…26 The observations were in line with that noted by . 27 Yu et al, based on a retrospective study involving 194 SLE patients and 71 healthy controls, have reported a significant positive correlation of SLEDAI with NLR, and a statistically significantly higher NLR in subjects with severe disease activity (>9 SLEDAI score) than mild disease activity (≤9 SLEDAI score). The current study has shown a significant correlation between SLEDAI and NLR.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that NLR may act as excellent indicator of inflammation status in various diseases, such as Crohn's disease (49), cancer (50,51), infection (52,53), and rheumatic diseases (54)(55)(56). Moreover, numerous studies also reported that NLR was closely related to inflammatory response and SLE disease activity (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Consistent with these previous studies, in this meta-analysis, we further demonstrated a close correlation of NLR with disease activity and lupus nephritis in SLE patients.…”
Section: ' Discussionmentioning
confidence: 99%
“…During the full-text review process, four studies were further excluded for lacking the data of interest. Finally, 14 studies with 1,781 SLE patients and 1,330 healthy controls were included in this meta-analysis (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations